2018
DOI: 10.1016/j.abrep.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of attempting to quit smoking among adults in Bangladesh

Abstract: BackgroundQuit attempts are very essential in population-based smoking cessation. Little is known about the correlates of making a quit attempt of smoking in Bangladesh. We aimed to examine correlates of making a quit attempt of smoking among adults in Bangladesh.MethodsWe used data from the 2009 Global Adult Tobacco Survey, Bangladesh. A total of 2217 adult current smokers (2141 males and 76 females) aged 15 years and older who participated in the survey were included. We compared socio-demographic, behaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
1
8
1
Order By: Relevance
“…Other studies also found that most smokers had tried to quit smoking and had made at least one attempt to quit [ 23 , 34 36 ]. A study in Bangladesh by Hakim et al found that intention to quit smoking was related to making an attempt to quit among adults [ 37 ]. Our study did not investigate the association between attempts and intention to quit, suggesting further research on this relationship is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also found that most smokers had tried to quit smoking and had made at least one attempt to quit [ 23 , 34 36 ]. A study in Bangladesh by Hakim et al found that intention to quit smoking was related to making an attempt to quit among adults [ 37 ]. Our study did not investigate the association between attempts and intention to quit, suggesting further research on this relationship is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The different approaches to changing smoking behaviour discussed above assume that the interventions involve incentives for people to coordinate their behaviour. 25 , 26 In this setting and many similar situations which involve coordination incentives, the influences of conformity and coordination incentives act in the same direction. In other situations, however, conformity and anticoordination incentives can act as countervailing influences.…”
Section: Conformity and Anticoordination Incentivesmentioning
confidence: 92%
“…Patle et al (2014) revealed that the overall population studied 221 out of 250 (88.4%, CI=0.48-1.28) was aware that tobacco is injurious to health, of which 97.34% were males and 81.02% were females. Hakim et al (2018) reported that Considering the knowledge and attitudes towards smoking, among current smokers who had attempted to quit, about 63.6% did not believe that smoking cause's serious illness, and 53.0% did not believe that cigarettes are addictive.…”
Section: Knowledge and Perception On Health Hazards Of Tobacco Usementioning
confidence: 99%